The Effect of Physical Activity on Depression Levels in the Elderly in Purbayan Village, Baki District, Sukoharjo Regency - Nanik Widyaningsih; Wachidah Yuniartika (Sean Institute, 2025)
An elderly person's health condition will decrease either naturally or due to illness. To anticipate this, a plan is needed with preventive efforts with the intention of keeping away from increasingly severe incidents including mental disorders . Activity the less will not be make physique and psychology elderly people experience penuretion, activity the good one For elderly that is daily activities which does not require energy big, tet a pi can provide for the elderly fitherating. The method used is a quantitative method. The purpose of this study was to determine the effect of physical activity on the level of depression in the elderly in Purbayan Village, Baki District, Sukoharjo Regency. The type of research in this study is pre- experimental before after study . The sample in this study was 30 elderly with the criteria of elderly who can communicate well, elderly who are not senile . The sampling technique was random sampling/probability sampling. Data collection in this study used a demographic data questionnaire and GDS (Geriatric Depression Scale), with 15 items . Data analysis used was descriptive and sample t-test . The results of the sample t-test , the significance value (two-tailed) showed the number (0.000) . The conclusion is that there is an influence between physical activity on the level of depression in the elderly in Purbayan Village, Baki District, Sukoharjo